Impact of bowel preparation type on the quality of colonoscopy: a multicenter community-based study. Issue 2 (1st January 2016) - Martin, Daniel; Walayat, Saqib; Ahmed, Zohair; Dhillon, Sonu; Asche, Carl V.; Puli, Srinivas; Ren, Jinma
Abstract : Background: High-quality bowel preparation is crucial for achieving the goals of colonoscopy. However, choosing a bowel preparation in clinical practice can be challenging because of the many formulations. This study aims to assess the impact the type of bowel preparation on the quality of colonoscopy in a community hospital setting. Methods: A retrospective, observational study was conducted utilizing a colonoscopy screening/surveillance database in central Illinois during the period of January 1, 2010, to March 31, 2014. Patients without bowel preparation assessment were excluded from this study. Controlling for the confounders, generalized linear models were used to estimate the adjusted impact [odds ratio (OR)] of bowel preparation type on the quality of preparation (excellent, good, fair, and poor), and on the detection of advanced adenoma. The association between the time of withdrawal after insertion and the quality of preparation was also examined using a linear model. Results: A total of 28, 368 colonoscopies; half the patients were male, and the average age was 61±9 years. Polyethylene glycol (PEG) was used in the majority (70.2%) of bowel preparations, followed by sodium sulfate (21.4%), sodium phosphate (2.5%), magnesium sulfate (0.4%), and others. Compared with PEG, magnesium sulfate had a poorer quality of bowel preparations (OR=0.6, 95% CI 0.4–0.9; p <0.05), whereas the quality of bowel preparation was significantly improved by using sodium sulfate (OR=5.7, 95% CI 5.4–6.1; p <0.001) and sodium phosphate (OR=2.1, 95% CI 1.8–2.5; p <0.001). For those who had adequate bowel preparation, the better quality of preparation significantly increased the detection rate of advanced adenoma (5.0, 3.6, and 2.9% for excellent, good, and fair, respectively). Conclusion: When possible, sodium sulfate–based preparations should be recommended in the community setting for colonoscopy because of their high quality of bowel preparation.